Ajvar in Focus on Branding Based on Consumer Habits - Dragana Đurić; Marko Pavlović; Milena Ilić; Miodrag Simić (Journal of Agronomy, Technology and Engineering Management)
The aim of this study is to identify guidelines for the branding of the Serbian product "Ajvar" based on research on consumer attitudes and habits. Methodologically, the research was conducted by surveying 186 respondents from Serbia and interviewing the manufacturer. A SWOT analysis was used to synthesize the findings. The results indicate that the majority of respondents (96.8%) expressed a preference for domestic Ajvar, while price is the key factor when making a purchase decision (72.6%). The majority of respondents are ready to pay a higher price for Ajvar with the BIO label (56.5%). Also, consumers prefer mild varieties of Ajvar and indicate the need to reduce salt and additives to make the product healthier. It was concluded that the branding of "Ajvar" should focus on educating consumers about the importance of the brand, improving the visual identity, and promoting its traditional and healthy values. This strategy contributes to a more secure placement for producers and greater consumer confidence. The branding of Serbian Ajvar represents an opportunity for positioning on the domestic and international market, which encourages the preservation of cultural heritage and the promotion of local products.